PENAFSIRAN AMINA WADUD PERSPEKTIF KESETARAAN GENDER TERHADAP AL-QUR’AN SURAH AL-NISA’ AYAT 34 - Zulpiana, Zulpiana; Hamnah, Hamnah; Maulana, Maulana (Borneo : Journal of Islamic Studies, 2024)
The aim of this research is to analyze Amina Wadud's interpretation of women's leadership from a gender equality perspective in Q.S. al-Nisa's verse 34. Women are always a problem that is influenced by the interpreter's subjectivity in interpreting verses of the Koran. So women are left behind and always put second. This is caused by the existence of a patriarchal culture, which considers men's roles to be more influential than women's roles. Q.S. al-Nisa's verse 34 is Amina Wadud's argument for allowing women to become leaders. This research uses a type of library research with qualitative methods. There are two data sources in this research, namely, primary and secondary data sources. The primary data sources in this research are the Qur'an and Women and Inside the Gender by Amina Wadud, while the secondary data are books, journals, theses, and articles related to this research. Apart from that, the data collection technique in this research uses library research. The data analysis technique used is the descriptive-analytical technique. The results of this research are first the meaning of women's leadership in Q.S. al-Nisa's verse 34 regarding the context of the household, which states that men are capable of protecting, guarding, and leading. Meanwhile, women's leadership in this case is only as a makmum and obeying their husband's orders. Second, the urgency of women's leadership is very necessary for the progress and development of the nation because it can create healthier and more egalitarian organizations so as to produce comprehensive decisions. Third, Amina Wadud's interpretation of women's leadership in Q.S. al-Nisa's verse 34 from the perspective of gender equality is that this verse is functional, meaning that male leadership only provides a living. However, if he is unable to do this, the qiwwamah within a man will be lost. The meaning of the verse will change according to existing conditions.